The effect of Echis coloratus venom on biochemical and molecular markers of the antioxidant capacity in human fibroblasts. Issue 1 (1st January 2017) - Ghneim, Hazem K.
ABSTRACT: This study was undertaken to examine the activities and levels of major antioxidants/oxidants in cultured human fibroblasts incubated with a sublethal dose of Echis coloratus venom (EcV). Glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD) and glutathione reductase (GR) activities and gene expression levels as well as reduced glutathione (GSH) levels, and the concurrent hydrogen peroxide (H2 O2 ), superoxide anions (SOA), lipid peroxides (LPO) and oxidized glutathione (GSSG) generation rates were assayed in fibroblast cultures and sonicates incubated with 0.5 µg ml –1 medium EcV for 4 h at 37°C. Data indicated that the activities of all antioxidant enzymes were significantly decreased and their corresponding transcripts downregulated in EcV-incubated cells compared to controls ( p < 0.001). In contrast, there were parallel equally significant increases in H2 O2, SOA and LPO generation rates in venom-incubated cells compared to controls ( p < 0.001). Additionally, GSH levels were significantly decreased and those of GSSG were equally significantly increased in venom-incubated cultures compared to controls ( p < 0.001) leading to a lowered GSH/GSSG ratio. In conclusion, incubation of fibroblast cultures with EcV resulted in a shift towards oxidative metabolism causing severe OS. This correlated with significant downregulation in the expression levels of all investigated antioxidant genes.